Mechanical Properties and Microstructure Evolution of Double-Sided Friction Stir Welding AA6061-T6 - Hendrato, Hendrato; Jamasri, Jamasri; Triyono, Triyono; Puspitasari, Poppy (Trans Tech Publications Ltd, 2022)
The Friction Stir Welding process has become very popular because it produces good welds with low defects and distortion. However, FSW in thick aluminium alloy plate joints such as those found in applications in the transportation industry such as automotive, rail, shipbuilding, and aircraft is more complex and challenging. Double-sided FSW has challenges to be developed and applying in the transportation industry. This study investigates the effect of different tool rotational speeds on the double-sided FSW of an Aluminium Alloy 6061-T6 thick plate. The ratios of the tool speed differences studied were 1:1, 1:1.3, and 1:1.6. Tensile strength, hardness, microstructure evolution, and fracture morphology were studied in this study. The investigation results concluded that an efficient and reliable double-sided FSW joint was achieved at joints with a tool rotational speed difference ratio of 1:1. © 2022 Trans Tech Publications Ltd, Switzerland.